2017
DOI: 10.1152/jn.00665.2016
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention during saccade decisions

Abstract: Behavioral measures of decision making are usually limited to observations of decision outcomes. In the present study, we made use of the fact that oculomotor and sensory selection are closely linked to track oculomotor decision making before oculomotor responses are made. We asked participants to make a saccadic eye movement to one of two memorized target locations and observed that visual sensitivity increased at both the chosen and the nonchosen saccade target locations, with a clear bias toward the chosen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 116 publications
5
19
0
Order By: Relevance
“…Our study has eliminated this potential criticism, and our observed deployment of attention in the opposite direction of the saccade and of the cue speaks in favor of the forward remapping effects. Consistent with previous behavioral studies (Baldauf and Deubel, 2008; Deubel and Schneider, 1996; Jonikaitis et al, 2017) and contrary to the convergent remapping effects, our results show that spatial attention is allocated to the saccade target and does not broadly spread around it. Additionally, convergent remapping cannot account for a number of earlier behavioral findings (Jonikaitis et al, 2013; Rolfs et al, 2011; Szinte et al, 2015; Szinte et al, 2016), as such spread of attention would have to be asymmetric and not spread towards the several control positions tested in these earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our study has eliminated this potential criticism, and our observed deployment of attention in the opposite direction of the saccade and of the cue speaks in favor of the forward remapping effects. Consistent with previous behavioral studies (Baldauf and Deubel, 2008; Deubel and Schneider, 1996; Jonikaitis et al, 2017) and contrary to the convergent remapping effects, our results show that spatial attention is allocated to the saccade target and does not broadly spread around it. Additionally, convergent remapping cannot account for a number of earlier behavioral findings (Jonikaitis et al, 2013; Rolfs et al, 2011; Szinte et al, 2015; Szinte et al, 2016), as such spread of attention would have to be asymmetric and not spread towards the several control positions tested in these earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our study has eliminated this potential criticism, and our results provide an unequivocal support for the forward remapping effects. Consistent with previous behavioral studies [31][32][33] and contrary to the convergent remapping effects, our results show that spatial attention is allocated to the saccade target and does not spread around it. Additionally, convergent remapping cannot account for a number of earlier behavioral findings [6][7][8][9] , as such spread of attention would have to be asymmetric and not spread towards the several control positions tested in these earlier studies.…”
Section: Discussionsupporting
confidence: 92%
“…Such pattern of results likely reflects competing selection between two parallel saccade targets, without observed inhibition. Indeed, a similar pattern of attentional selection is also observed in saccadic free-choice tasks that do not require any saccadic inhibition (Jonikaitis et al 2017). In our task, in contrast, we observed clear inhibition of saccades and attention.…”
Section: Discussionsupporting
confidence: 85%